2014
DOI: 10.1039/c3cp53653j
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the fundamental physical chemistry in heterogeneous photocatalysis: its thermodynamics and kinetics

Abstract: Although the history of photocatalysis research is not so long, many researchers have studied photocatalysis and a large number of papers on photocatalysis have been published. The objectives of this review paper are to revisit the fundamentals of photocatalysis, especially its thermodynamics and kinetics, which have not been reexamined in recent studies, to clarify the problems, if any, that prevent developments in the field of photocatalysis, and to present insights for future progress. What we know and we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 38 publications
(23 reference statements)
1
97
0
10
Order By: Relevance
“…When such an n-type semiconductor is immersed, or in contact in an electrolyte solution, electrons in the donor levels go out to the electrolyte since the donor level in an n-type semiconductor may be more cathodic than the electrode potential of electrolyte solutions. This flow of electrons in the donor level to an electrolyte results in the formation of a so-called Schottky-type barrier [10] at the interface to prohibit electron flow from an electrolyte to an electrode, i.e., potential slope due to an electron-deficient so-called depletion layer is built in a semiconductor. …”
Section: Donor Levels In An N-type Semiconductormentioning
confidence: 99%
See 1 more Smart Citation
“…When such an n-type semiconductor is immersed, or in contact in an electrolyte solution, electrons in the donor levels go out to the electrolyte since the donor level in an n-type semiconductor may be more cathodic than the electrode potential of electrolyte solutions. This flow of electrons in the donor level to an electrolyte results in the formation of a so-called Schottky-type barrier [10] at the interface to prohibit electron flow from an electrolyte to an electrode, i.e., potential slope due to an electron-deficient so-called depletion layer is built in a semiconductor. …”
Section: Donor Levels In An N-type Semiconductormentioning
confidence: 99%
“…The rate of photoinduced silver metal deposition was analyzed using a Stern-Volmer plot, a popular method in the field of photochemistry; almost linear double-reciprocal plots of the (apparent) quantum efficiency for the deposition (Ф) as a function of concentration of silver ion (Ag + ) in solutions (C Ag ) were obtained for both TiO 2 and ZnO crystals, as (9) where Ф lim , and C L are constants. In the first approximation for interpretation of the meaning of Equation 9, the authors assumed a reaction mechanism in which electrons photoexcited by the efficiency  react with surface-adsorbed Ag + (with the surface concentration N Ag ) to give deposits with a rate constant k 3 , otherwise e − is deactivated with a rate constant k 4 , as (10) This equation can be derived by "steady-state (stationary-state) approximation", which is often employed for reactions induced by short-lived active species such as the photoexcited state of a given material (e − and h + in a photocatalyst), based on the assumption of a constant concentration of e − that is produced by photoabsorption of a photocatalyst and consumed by (a) surface reaction and (b) recombination with holes. Thus, the rate of photocatalytic reaction is governed by the rate of recombination (k 4 ), though analysis of actual data using Equation 10 gives only the ratio of rate constants, k 3 /k 4 .…”
Section: Rate-determining Step In Photocatalysis and Steady-state Appmentioning
confidence: 99%
“…Thus, what is the source of the author's frustration? Possible reasons, mainly misunderstandings, misconceptions, and/or speculation in a scientific sense, have been pointed out in the present author's recent review papers [2][3][4][5]. This short review presents new misconceptions often found in discussions of photocatalysis studies that have not yet been recognized by such papers' authors.…”
Section: Introductionmentioning
confidence: 89%
“…The turnover numbers (TONs) for 5 h photocatalytic O 2 gas evolution reactions were estimated as the total moles of substrates (H 2 O) consumed over the reaction per moles of active catalytic species (CoO x ) [17,18]:…”
Section: Photocatalytic Water Oxidation Activity Testmentioning
confidence: 99%